Antibacterial effects of platelets on five common pathogenic bacteria: a comparative analysis - LIU Erxiong; WANG Wenting; XU Jinmei; AN Ning; WANG Yafen; SHI Jieyun; ZHANG Lingling; CHEN Yaozhen; YIN Wen (Zhongguo shuxue zazhi)
[Objective] To compare and analyze the antibacterial effects of platelets against five common clinical pathogenic bacteria including MRSA, SE, SA, E. coli, and CRKP, and to preliminarily explore the role of DCD sensitivity in the observed variations of antibacterial effects. [Methods] The same number of platelets were used to establish co-culture systems of platelets and platelet lysates with the five pathogenic bacteria. The antibacterial effects of platelets and platelet lysates on the five pathogenic bacteria were evaluated by observing the turbidity of the bacterial solution, measuring the OD600 nm value of the bacterial solution and counting the colonies. The supernatant protein of platelets co-cultured with MRSA was collected for quantitative proteomics analysis to explore the important antibacterial proteins of platelets. The content of DCD in the supernatant after co-culture of platelets and platelet lysates with the five pathogenic bacteria was detected by ELISA to preliminarily analyze the reasons for the different antibacterial effects of platelets on the five pathogenic bacteria. [Results] Compared with the control group of MRSA, SA, and SE, the turbidity of the bacterial solution decreased after co-culture of platelets and platelet lysates with MRSA, SA, and SE for 12 h, and the OD600 nm value and colony count were significantly reduced (P<0.05). The turbidity of the bacterial solution did not change significantly after co-culture of platelets and platelet lysates with E. coli for 24 h, but the OD600 nm value decreased (P<0.05), and the colony count decreased to 108 CFU/mL but the difference was not statistically significant (P>0.05). Compared with the control group of CRKP, the turbidity, OD600 nm value, and colony count of the bacterial solution did not change significantly after co-culture of platelets and platelet lysates with CRKP (P>0.05). Proteomics results showed that after co-culture with MRSA, important proteins related to platelet activation, including collagen, fibrinogen, von Willebrand factor, integrin αIIbβ3, platelet glycoprotein V and IV were significantly up-regulated. ELISA results showed that after co-culture with the five pathogenic bacteria, platelets could secrete a large amount of DCD, with the content around 3 μg/mL. [Conclusion] The antibacterial effect of platelets on Gram-positive bacteria MRSA, SA, and SE is better than that on Gram-negative bacteria E. coli and CRKP, and platelets have the best antibacterial effect on MRSA. The differences in antibacterial effects of platelets on the five pathogenic bacteria may be related to the sensitivity of DCD antibacterial peptides to the five pathogenic bacteria.